Total Physical Response (TPR): How is it used to Teach EFL Young Learners? - Astutik, Yuli; Megawati, Fika; Aulina, Choirun Nisak (International Journal of Learning, Teaching and Educational Research, 2019)
When teachers teach the English vocabulary about parts of the body, they use rhythm and body movements while mentioning its name. It is called Total Physical Response (TPR) method. This article investigates the implementation of the TPR method used by three teachers in teaching English vocabulary to young learners. Additionally, the researchers investigated the problems faced by the three teachers as well as potential solution for those problems. In this research, the researchers used qualitative descriptive to understand the way teachers implemented TPR in their classrooms. Data from this study indicates that, from the thirteen principles of TPR method found that; Teacher 1 (T1) used seven principles in the 1st observation and six principles in the 2nd observation, and Teacher 2 (T2) only used one principle in the 1st observation and two principles in the 2nd observation. Then, Teacher 3 (T3) used two principles both in the 1st and the 2nd observation. The difficulties faced by those three teachers implementing TPR stemmed from their lack of understanding about the implementation of the TPR method even they did not distinguish the appropriate theoretical basis of TPR. Finally, to address challenges in implementing TPR, the teachers expect additional training related to teaching English to young learners especially with a specific theory related to TPR method so that they can implement it well and have more practice with the principles of TPR method in teaching English to young learners. https://doi.org/10.26803/ijlter.18.1.7